2010
DOI: 10.1159/000306058
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of INTERSTROKE: A Global Case-Control Study of Risk Factors for Stroke

Abstract: Stroke is a major global health problem. It is the third leading cause of death and the leading cause of adult disability. INTERHEART, a global case-control study of acute myocardial infarction in 52 countries (29,972 participants), identified nine modifiable risk factors that accounted for >90% of population-attributable risk. However, traditional risk factors (e.g. hypertension, cholesterol) appear to exert contrasting risks for stroke compared with coronary heart disease, and the etiology of stroke is far m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 128 publications
2
79
0
2
Order By: Relevance
“…The limited size of the neuroimaging sub-cohort further affected the strength of statistical associations of cognitive outcome in the cohort. Nonetheless, cases with and without neuroimaging were quite similar statistically, and our cohort shares similar demographic and phenomic characteristics with stroke cases described earlier in Nigeria [72] and sub-Saharan Africa [23]. Follow up of our cohort is currently in progress to explore the early evolution of cognitive dysfunction and the determining factors.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The limited size of the neuroimaging sub-cohort further affected the strength of statistical associations of cognitive outcome in the cohort. Nonetheless, cases with and without neuroimaging were quite similar statistically, and our cohort shares similar demographic and phenomic characteristics with stroke cases described earlier in Nigeria [72] and sub-Saharan Africa [23]. Follow up of our cohort is currently in progress to explore the early evolution of cognitive dysfunction and the determining factors.…”
Section: Discussionsupporting
confidence: 67%
“…Confirmation of cardiovascular risk factors (hypertension, diabetes mellitus, atrial fibrillation, dyslipidemia, cigarette smoking, and alcohol use) were based on self-report, use of relevant medications and review of medical notes. Lifestyle factors including nutritional status and physical activity were assessed according to the design of the INTERSTROKE Study [23]. Dietary patterns were assessed in all subjects with a food frequency questionnaire assessing the frequency of different types of food taken by the subjects in the prior year before the onset of stroke (and separately in the three months period after stroke) with appropriate addition of common local foods and delicacies to relevant categories.…”
Section: Subject Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is a major global health problem [1,2] , and white matter hyperintensities (WMHs) are receiving increasing attention as a risk factor for stroke [2][3][4][5][6][7][8][9][10][11] . Furthermore, WMHs are associated with cognitive impairment, silent brain infarction (SBI), cerebral microbleeds, a poor functional outcome after stroke, and mortality [2][3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The 12 articles considered in this review reported on five separate studies: INTERHEART (8,(11)(12)(13)(14)(15) INTERSTROKE, (16) the WHO Collaborative Study of Cardiovascular Disease and Steroid Hormone Contraception (17)(18)(19) and two unnamed studies. (20,21) Only INTER-…”
Section: Resultsmentioning
confidence: 99%